Social Determinants of Health and Cerebral Small Vessel Disease: Is Epigenetics a Key Mediator? - Livia Parodi; Ernst Mayerhofer; Kaavya Narasimhalu; Nirupama Yechoor; Mary E. Comeau; Jonathan Rosand; Carl D. Langefeld; Christopher D. Anderson (Journal of the American Heart Association: Cardiovascular and Cerebrovascular Disease, 2023)
Cerebral small vessel disease is highly prevalent, particularly in marginalized communities, and its incidence is expected to increase given the aging global population. Cerebral small vessel disease contributes to risk for stroke, vascular cognitive impairment and dementia, late‐life depression, and gait disorders. A growing body of evidence suggests that adverse outcomes, including cerebral small vessel disease, caused by traditional cardiovascular risk factors are at least partly mediated by epigenetic changes, some of them already beginning during fetal development. Societal and health care access inequities, summarized under the umbrella term social determinants of health, put a higher burden of cardiovascular risk factors on marginalized populations and expose them to an increased risk for adverse outcomes. Social epigenetics has begun to deliver solid evidence that social determinants of health lead to distinct epigenetic signatures that potentially mediate the biological effect of environmental exposures on cardiovascular risk factors. Here, we provide a review of the most recent advances in the epigenetics of cerebral small vessel disease risk factors and social determinants of health and call for research efforts combining insights from both fields to reach a deeper understanding of the causal pathways, ultimately facilitating discovery of new treatment targets for a disease whose burden is magnified by existing health disparities.